PENINGKATAN HASIL BELAJAR MATEMATIKA PADA MATERI KECEPATAN DAN DEBIT MELALUI MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) DI KELAS VB SDN KALIMULYA 5 DEPOK - Devi Arrianti; Winda Amelia (Universitas Trilogi, 2021)
This Classroom Action Research (CAR) was conducted in Class VB SDN Kalimulya 5 Depok on mathematics subject to speed and discharge. The focus of the problem raised in this study is the improvement of mathematics learning outcomes in the material speed and discharge through the Numbered Head Together (NHT) learning model. In this study, researchers used a class action research method consisting of two cycles. Each cycle consists of Planning, Action, Observation, and Reflection. Data collection in this study came from student learning outcomes, interview results, observation sheets and documentation. The findings obtained from research conducted using the Numbered Head Together (NHT) learning model are the results of learning in mathematics subject matter speed and discharge have increased. It is proven from the pre cycle that the number of students who have successfully reached KKM is only 8 students (33.3%), in the first cycle the number of students who have successfully reached KKM has increased by 16 students (66.6%) but has not yet reached the specified criteria of 85% students must be complete. Then, in the second cycle as many as 21 students (87.5%) had successfully reached the KKM. In the second cycle the criteria that have been determined have been achieved.